Decontamination of wastewater containing contaminants of emerging concern by electrooxidation and Fenton-based processes – A review on the relevance of materials and methods. (November 2022) - Santos, Mauro C.; Antonin, Vanessa S.; Souza, Felipe M.; Aveiro, Luci R.; Pinheiro, Victor S.; Gentil, Tuani C.; Lima, Thays S.; Moura, João P.C.; Silva, Carolina R.; Lucchetti, Lanna E.B.; Codognoto, Lucia; Robles, Irma; et al.
Abstract: In recent years, there has been an increasingly growing interest regarding the use of electrochemical advanced oxidation processes (EAOPs) which are considered highly promising alternative treatment techniques for addressing environmental issues related to pollutants of emerging concern. In EAOPs, electrogenerated oxidizing agents, such as hydroxyl radical (HO ), can react non-selectively with a wide range of organic compounds, degrading and mineralizing their structures to unharmful molecules like CO2, H2 O, and inorganic ions. To this date, a broad spectrum of advanced electrocatalysts have been developed and applied for the treatment of compounds of interest in different matrices, specifically aiming at enhancing the degradation performance. New combined methods have also been employed as alternative treatment techniques targeted at circumventing the major obstacles encountered in Fenton-based processes, such as high costs and energy consumption, which still contribute significantly toward inhibiting the large-scale application of these processes. First, some fundamental aspects of EAOPs will be presented. Further, we will provide an overview of electrode materials which have been recently developed and reported in the literature, highlighting different anode and cathode structures employed in EAOPs, their main advantages and disadvantages, as well as their contribution to the performance of the treatment processes. The influence of operating parameters, such as initial concentrations, pH effect, temperature, supporting electrolyte, and radiation source, on the treatment processes were also studied. Finally, hybrid techniques which have been reported in the literature and critically assess the most recent techniques used for evaluating the degradation efficiency of the treatment processes. Graphical abstract: Image 1 Highlights: Electro-Fenton and Oxidation Processes removing contaminants of emerging concern. An overview of recently developed electrode materials is provided. The combination of methods to provide hybrid processes is summarized. The most recently used techniques to evaluate degradation efficiency are discussed.